Threat of Fusarium pallidoroseum on Post-Harvest Kola Nut (Cola spp.) in Nigeria: A Review - Sulaimon, Sheriff Olalekan; Ajadi, Ibrahim; Mubarak, Yahya; Bello, Habibat Bolanle; Ibrahim, kazeem (Sahel Journal of Life Sciences FUDMA, 2024)
Fusarium pallidoroseum poses a significant risk to Kola nut production, impacting both quality and quantity. This review explores the pressing threat of Fusarium pallidoroseum on post-harvest Kola nut (Cola spp.) in Nigeria. By identifying knowledge gaps and challenges in current management approaches, this review underscores the necessity for further research and collaboration among stakeholders to develop sustainable and effective control measures. Addressing the menace of Fusarium pallidoroseum on post-harvest Kola nut is crucial for safeguarding agricultural sustainability, promoting food security, and protecting the livelihoods of farmers in Nigeria.